2007
DOI: 10.1017/s0007114507832922
|View full text |Cite
|
Sign up to set email alerts
|

Dietary microparticles and their impact on tolerance and immune responsiveness of the gastrointestinal tract

Abstract: Dietary microparticles are non-biological bacterial-sized particles of the gastrointestinal lumen that occur due to endogenous formation (calcium phosphate) or following oral exposure (exogenous microparticle). In the UK, about 40 mg (1012) of exogenous microparticles are ingested per person per day, through exposure to food additives, pharmaceutical/supplement excipients or toothpaste constituents. Once ingested, exogenous microparticles are unlikely to pass through the gastrointestinal tract without adsorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 31 publications
0
50
0
5
Order By: Relevance
“…These have previously been considered immunologically inert, but accumulating evidence suggests that ingested microparticles are taken up by the intestinal mucosa and induce an immunological response. 64 It was shown that conjugates of titanium oxide microparticles and lipopolysaccharide increase secretion of IL-1b in intestinal mucosal organ cultures. 65 Moreover, a higher microparticleinduced release of IL-1b was seen in IBD explants.…”
Section: Discussionmentioning
confidence: 99%
“…These have previously been considered immunologically inert, but accumulating evidence suggests that ingested microparticles are taken up by the intestinal mucosa and induce an immunological response. 64 It was shown that conjugates of titanium oxide microparticles and lipopolysaccharide increase secretion of IL-1b in intestinal mucosal organ cultures. 65 Moreover, a higher microparticleinduced release of IL-1b was seen in IBD explants.…”
Section: Discussionmentioning
confidence: 99%
“…Sources may be tablets, milk whitener and toothpaste among others. Other authors estimate the daily ingested amount of both TiO 2 and AlSi to be 40 mg or 10 12 particles/person/day [44,45]. …”
Section: Sources Of Dietary Microparticlesmentioning
confidence: 99%
“…Another dietary factor that seems to be implicated in the etiopathogenesis of IBD and particularly that of CD is exogenous dietary microparticles (97). These are defined as non-biological particles of the gastrointestinal lumen with an appropriate size and shape which are taken up by mucosal phagocytes.…”
Section: Exogenous Microparticle Hypothesismentioning
confidence: 99%